Availability of cosmetic treatment using novel cosmetics-based material on patients with craniofacial concavity. Issue 3 (July 2018) - Koyama, Shigeto; Kanetaka, Hiroyasu; Sagehashi, Yoshinori; Sasaki, Keiichi; Sato, Naoko
Abstract: Purpose: Patients treated with maxillofacial prosthetics often experience emotional problems because of the remaining facial skin concavity such as a surgical scar. In such cases, cosmetic treatment can potentially correct their skin tone imperfections and deformities. This study aimed to evaluate the clinical availability of novel cosmetics-based material for craniofacial small concavity by initiating a cosmetic treatment in a preliminary case. Methods: Eighteen patients with aesthetic problems such as craniofacial deformities, small defects, and concavities on their faces underwent cosmetic treatment that was performed by makeup practitioners. Data were collected from the patient's charts and a survey questionnaire. A visual analog scale was used to conduct a survey regarding the satisfaction levels of the patients following cosmetic treatment with a novel cosmetics-based material. The cosmetic treatment was performed for a concavity on the left midface of a 67-year-old woman with partial maxillectomy. The novel cosmetics-based material was manufactured from a semi-translucent oil base. Results: The satisfaction level of the patient increased after undergoing the cosmetic treatment. Regarding clinical applications, the novel cosmetics-based material can help reduce their cosmetic disturbance and restore the small deformity. Conclusions: These results suggest that the cosmetic treatment with the novel cosmetics-based material can be used as a subsidiary method for facial prostheses or an independent new method for correcting patients' small craniofacial concavity and for reducing visible deformity.